Indikator Ekonomi Subsektor Perikanan Tangkap Indonesia di Masa Pandemi Covid-19 Tahun 2020 - Miko Novri Amandra; Bayu Rhamadani Wicaksono; Evita Choiriyah; Penny Wulandari (Politeknik Statistika STIS, 2021)
The disruption of economic activities during the Covid-19 pandemic has caused the fisheries subsector in Indonesia, which is dominated by small scale fishers, to be vulnerable to poverty. A particular study is needed to measure the purchasing power of fishers through the fisher’s term of trade (NTN). The fluctuations of NTN can be affected by several factors, including the household consumption index (IKRT), the value of fisheries exports, and the increasing number of Covid-19 active cases. This study aims to measure the short-term and long-term effects of those factors on NTN during the Covid-19 pandemic and the speed of convergence of province’s NTN. The analysis used is dynamic panel data regression on monthly data 2020 from 34 provinces in Indonesia. This study shows that the value of fisheries exports has a short-term effect on NTN, while the increasing number of Covid-19 active cases has short-term and long-term effects on NTN. The NTN gaps between provinces is reduced by 17.21 percent per month and reaches half time convergence within 4 months.